The emergence of God"s new people: The beginnings of Christianity reconsidered - Stegemann, Wolfgang (HTS teologiese studies, 2006)
The article deals with the problem of the Christian beginnings. Unlike many other scholars, the article does not defend the traditional metaphor which compares Judaism and Christianity to the relationship of mother and daughter. It also does not take for granted that ancient Judaism and Christianity can be viewed as religious. The category “religion” is a modern concept and therefore does not meet the ancient discourse. The article aims to argue that the emergence of Christianity could be better understood in terms of “ethnicity”. Another version of the article was published in Di storia dell' esegesi 21(2), 2004, 497-513.Jede Vorstellung von Anfängen verleitet dazu eine Fabel zu konstruieren (Jean Starobinski)